Meningkatkan Keterampilan Berpikir Kritis melalui Pembelajaran Diferensiasi dengan Orientasi Pemecahan Masalah Terintegrasi dengan MISCards (OPTIMIS) pada Murid Kelas XI SMA Negeri 1 Bone Tahun Pelajaran 2024/2025 - Ningsi, Surya; Danial, Muhammad; Arismunandar, Arismunandar; H, Nurhikmah (Chemistry Education Review (CER), 2024)
Teachers have a very important role in guiding the growth and development of the potential of each student. Students have different ways of understanding what has been taught. This difference is not a barrier for teachers in teaching. On the contrary, it is an encouragement for teachers to be more creative and innovative in designing learning that suits students' learning needs. Creating student-centered learning can be done through differentiated learning. MIScards integrated problem solving-oriented differentiation learning (OPTIMIS) in chemistry learning on the Stoichiometry topic subtopic Mole Concept was carried out on class XI students at SMA Negeri 1 Bone for the 2024/2025 academic year. MIScards is a learning aid in the form of developing interactive card media that is designed visually, attractively and interactively using Canva by optimizing both sides of the card. Before the learning process is carried out, students are given an initial cognitive and non-cognitive assessment. From the results of the assessment, a differentiation design for content, processes and products was carried out using the differentiation learning canvas. This learning process uses the Problem Solving and Problem Based Learning models. The good practice of differentiation learning with OPTIMIS, which is implemented at UPT SMAN 1 Bone, produces effective results. Students are more critical in solving problems collaboratively, creatively and have an impact on a better learning ecosystem.